JENIS DAN POPULASI HAMA LALAT BUAH (Bactrocera spp.) PADA TANAMAN JERUK (Citrus nobilis Lour) DI DESA KUOK KECAMATAN KUOK KABUPATEN KAMPAR - Juliani Harahap; Hafiz Fauzana; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Fruit flay is a pests of the citrus orange in Kampar District. Observation species and population fruit fly pest to determine the pest control. This study aims to determine the type and population fruit fly (Bactrocera spp.) That attack citrus plants and fruit flies attack percentage in the village of Kuok, Kampar. Research has been conducted with a purposive sampling method with the criteria citrus orchards and attack fruit fly pests. The observation did on two gardens to be attacked with fruit flay that Rudi pack with an area of 0.5 ha and 0.25 ha Ahmad garden with a distance that is 6 x 6 m. Plant samples selected systematically method with zig-zag pattern. Intake of fruit flies imago done in two ways: first, by making use of petrogenol traps the observed daily for 7 days. Second, making fruit on the ground attacked performed once at the start of the study. The parameters measured were the description of the location, species and population fruit fly, the percentage of attacks. Datas were analyzed statistically do tabulation and calculated the average population and deskription in tables, and images. The results of such studies fruit flies were caught in the petrogenol trap is B. carambolae, B. papayae and B. umbrosa. Species B. carambolae the highest population obtained in the village of Kuok, percentage of fruit flies attack on citrus plant in the village of Kuok relatively low at 3.42%. Keywords: Citrus nobilis Lour, Bactrocera spp., Species and populations